Dental Hygiene Care Intervention (Oral Hygiene) in Reduction Plaque Index towards Hearing Impaired Students: RCT - Nurhamidah Nurhamidah; Henry Setyawan; Lanny Sunarjo (UPPM Poltekkes Kemenkes Semarang, 2015)
This research was to determine the influence of dental hygiene care interventions (oral hygiene) to the reduction of plaque index of deaf students. It was a true experimental with randomi pre-post-test control group design. The measurements of plaque index performed with PHPM index in inspection sheet method. The plaque index are calculated from the amount of plaque scores in inspection sheet. Research was done over 49 respondents that divided into two groups: intervention groups and control groups. There was a significant difference of plaque index before and after the treatment. In intervention groups it decreased from the average of 35,7 to 10,4 (70,87%) with value p=0,001. Whether in control group it was also decreased from the average of 37,5 to 28,9 (22,93%) with value p=0,001. The average of plaque index reduction was also differ significantly between intervention groups (31,06 ) and control groups (12,0) with value p=0,001. Dental hygiene care intervention (oral hygiene) can reduce plaque index of deaf students. Suggestion: Dental hygiene care intervention (oral hygiene) should be delivered periodically to the deaf students by nurturing the habit brushing teeth twice a day completed with a written module, so that it can prevent the occurrence of oral diseases.